Instrumen Derivatif dan Mekanisme Hedging dalam Perspektif Syari’ah Islam - Kusumastuti, Dani (Fakultas Syariah IAIN Purwokerto, 2008)
The application of derivative instruments have been broadly expanded. As a hedging instrument, it is now becomes so far as an investment instrument that traded in the market in massive volume. Major of Islamic scholars have found them to be objectionable based on the juridical nature of contractual arrangements. This paper explains the expanding function of contemporary derivatives and reviews the scholars legal point of view. This paper also defines the basic norms of Islamic financial ethics as the guidance for developing Islamic financial instrument. In the last section of this paper examines alternative for Islamic hedging based on salam and al-khiya>r principles, which completed by syari’ah insurance.